Diaphragmatic paralysis due to spinal muscular atrophy. An unrecognised cause of respiratory failure in infancy?. Issue 2 (February 1985) - McWilliam, R C; Gardner-Medwin, D; Doyle, D; Stephenson, J B
Abstract : An unusual form of spinal muscular atrophy presenting with respiratory failure was observed in four infants from two families. In one, whose death was attributed to pneumonia, the diagnosis was inferred retrospectively after two siblings died from an identical illness and were shown to have diaphragmatic paralysis and the typical electrophysiological and histological features of spinal muscular atrophy. Other signs of skeletal muscular weakness were absent or inconspicuous. The fourth, unrelated infant presented in an identical way but has survived for over a year on a ventilator. Two months after the onset of respiratory paralysis, more extensive skeletal muscular weakness was seen. Other infants, dying of unexplained respiratory illness, may have this disorder and some may be included in the miscellany of disorders that constitute the sudden infant death syndrome.